ANTECEDENTS OF CONSUMER-BASED ELECTRONIC RETAIL BRAND EQUITY: AN INTEGRATED MODEL - Muhammad Mohsin Butt,; Yu Yingchen,; Amrul Asraf Mohd-Any,; Dilip S. Mutum,; Hiram Ting,; Khong Kok Wei, (Asian Academy of Management Journal, 2018)
The purpose of this study is to test and compare multiple conceptual models that examine the relationships among electronic retail (e-retail) service quality, trust, satisfaction, and consumer-based e-retail brand equity. A quantitative survey was conducted among Chinese online shoppers. The survey used established scales to measure constructs in the proposed models. Structural equation modelling (SEM) procedure was applied to test alternate models. The results confirmed that web design and customer service positively influence satisfaction, while fulfilment and security dimension of e-retail quality influence consumer trust. Both trust and satisfaction were found to be significant influencers of consumer-based e-retail brand equity. E-retailers can use this model to measure, monitor, and improve their consumer’s perceptions towards their brand. This study contributes to the existing literature that deals with antecedents of online consumer-based retail brand equity. It adds value by proposing and testing multiple models of online consumer-based brand equity which is rare in e-brand equity research.